Human body-gesture capacity: the tense – lax distinction: a preliminary outline of research work - Puppel, Joanna (Scripta Neophilologica Posnaniensia, 2019)
In phonology, the terms ‘tenseness’ (tensing) and ‘laxness’ (laxing) are an important pair pertaining to the distinctive features of vowels. A similar dichotomy, ‘tenseness’ – ‘laxness’, can also be observed in the body-gesture (B-G) behaviors. On the basis of this distinction, the author of the article proposes to make a division between two body–gesture cultures, namely: the ‘lax B-G cultures’, and the ‘tense B-G cultures’, respectively. Additionally, the author constructs two working hypotheses. Namely: Hypothesis no. 1 (H1): (H1a): The laxer the B-G system is, the less ritual (and more casual) a given communication act happens to be. (H1b): The relationship “lax body posture + lax gesture” correlates with full spoken, profane (non-ritual) communication potential. Hypothesis no. 2 (H2): (H2a): The tenser the B-G system is, the more ritual a given communication act happens to be. (H2b): The relationship “tense body posture + tense gesture” correlates with full spoken, ritual (nonprofane) communication potential.